P1.51 Antimicrobial resistance (AMR) and NG-MAST profile of neisseria gonorrhoeae isolates collected from std patients from across india. (8th July 2017) - Sood, Seema; Mahajan, Neeraj; Bala, Manju; Singh, Rajendra; Kapil, Arti; Sreenivas, V; Kar, Hemanta Kumar; Sharma, Vinod Kumar
Abstract : Introduction: Neisseria gonorrhoeae multiantigen sequence typing (NG-MAST) is a highly discriminatory technique for assessing the genetic diversity of N. gonorrhoeae (NG) and has also been put forward as a tool for predicting specific antimicrobial resistance (AMR) phenotypes. In light of the above, the present study was undertaken to investigate the molecular epidemiology of NG in India and to examine if it can be used as a means for predicting AMR. Methods: A total of 204 consecutive NG isolates collected between April 2010 - October 2013 were investigated. Antimicrobial susceptibility testing was done using disc diffusion method and E test and the results interpreted using the breakpoint criteria of CDS technique. NG-MAST was performed as described previously. WHO N. gonorrhoeae reference strains F, G, K-P were used as controls. Association between NG-MAST sequence type (ST) and antimicrobial susceptibility was probed using χ 2 and fisher's exact tests. Results: Rates of resistance to classical antibiotics were high. Decreased susceptibility (DS) to ceftriaxone (MIC 0.032–0.25 µg/ml) was seen in 7.3% while azithromycin resistance (MIC ≥1 µg/ml) in 2.5% isolates. A total of 202 NG isolates were assigned into 108 different STs while 2 were not typable, The high genetic diversity arose from the allelic combination of 80 por and 44 tbpB alleles and the overall mean genetic distance was 85.5 (SE 4.6) nucleotide differences. Out of 108 STs, 84 (77.8%) were novel. The majority of STs (75.9%, 82 of 108) were represented by singletons, whereas the remaining STs included between 2 and 38 isolates. The most common STs were ST6058 (n=38, 18.8%), ST2990 (n=6, 2.9%), ST6069, ST9775, ST9783, ST9875 (n=5, 2.5% each). There was a significant association between ST6058 and resistance to penicillin (p=0.00) and tetracycline (p=0.00) and ST6069 and ST 6083 and DS to ceftriaxone (p=0.00 and p=0.01 respectively). Conclusion: The present study highlights a heterogeneous gonococcal population in India. Our data, although on a limited number of NG isolates, testify to an association between genotype and AMR phenotype.